Trazos psicopáticos en jóvenes y pertenencia a grupos de pares antinormativos - Andrade Ferraz, Cristiana Isabel (2022)
The objective of this investigation was to establish a relationship between psychopathic traits and belonging to groups of antinormative peers in a sample of Portuguese adolescents. Were included 517 adolescents from the schools in the north of Portugal, aged between 12 and 18 years. Was used the Escala de Antinormatividade Grupal (EAG) and the Youth Psychopathic Inventory Traits Reconstruted (YPI-RE). The results indicated gender and age influences at the level of the Group Antinormativity and psychopathic traits, and parent´s marital status at the level of psychopathic traits. There was a significant positive correlation between Group Antinormativity and psychopathic traits, and, finally, it was concluded that Irresponsibility, the Search of Danger and to be male predict Group Antinormativity.